Mutable Lewis and Brønsted acidity of aluminated SBA-15 as revealed by NMR of adsorbed pyridine-15N - Gurinov, Andrey A (Langmuir : the ACS journal of surfaces and colloids, 2011)
© 2011 American Chemical Society